Yang-Mills theory from super moduli space - Carlo Alberto Cremonini; Ivo Sachs (Journal of High Energy Physics)
Abstract For the spinning superparticle we construct the pull-back of the world-line path integral to super moduli space in the Hamiltonian formulation. We describe the underlying geometric decomposition of super moduli space. Algebraically, this gives a realization of the cyclic complex. The resulting space-time action is classically equivalent to Yang-Mills theory up to boundary terms and additional non-local interactions.